2017
DOI: 10.24925/turjaf.v5i7.745-749.1152
|View full text |Cite
|
Sign up to set email alerts
|

Bor Gübrelemesinin Şeker Pancarında (Beta vulgaris L.) Verim Özellikleri Üzerine Etkisi

Abstract: Bu çalışmada, bor uygulamalarının şeker pancarında azot, fosfor, potasyum konsantrasyonu ile verim üzerine etkileri araştırılmıştır. Çalışma Gaziosmanpaşa Üniversitesi Ziraat Fakültesi arazisinde toprak taksonomisine göre tipik ustifluvent alt grubuna ait topraklar üzerine kurulmuştur. Deneme, tesadüf blokları deneme desenine göre 3 tekerrürlü olarak 4 farklı dozda bor (0, 0,18, 0,27 ve 0,36 B kg da The Effects of Boron Fertilizatıon to Yield Properties in Sugar Beet (Beta vulgaris L.) A R T I C L E I N F O A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…Boron is a prerequisite for sugar beet yield and sugar contents. B application was found to benefit growth traits and root yield of sugar beet, while its deficiency resulted in the decreased growth and biomass of sugar beet (Lawson 2010;Durak and Karan 2017). In this trial, it was found that B deficiency hindered growth characteristics of sugar beet as the treatment time increased and the most pronounced effects were noted under B1 (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Boron is a prerequisite for sugar beet yield and sugar contents. B application was found to benefit growth traits and root yield of sugar beet, while its deficiency resulted in the decreased growth and biomass of sugar beet (Lawson 2010;Durak and Karan 2017). In this trial, it was found that B deficiency hindered growth characteristics of sugar beet as the treatment time increased and the most pronounced effects were noted under B1 (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…The B deficiency becomes visible on leaf and beet as called heart and dry rots, which seriously affects the yield and sugar content, so it is imperative to determine the symptoms of leaf stress in sugar beet and regulate them as soon as possible (Lawson 2010). Most of the research on the effects of B on sugar beet had been conducted in field trials, focusing on aspects such as yield, quality, and the effects of foliar B application (Abido et al 2012;Durak and Karan 2017). Nevertheless, Studies have been investigated in hydroponics, particularly at the seedling stage (Rerkasem et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Borlu gübre verilmiş topraklarda ekilen bitkilerde tozlanma, meyve tutumu, meyve verimi ve meyvelerin kalitesi artar [10]. Fındıkta borlu gübrelemenin boş meyve oluşumunu azaltarak verim üzerinde etkili olduğu [11], kirazda meyve kalitesini ve görünümlerini iyileştirdiği [12], domatesin verimini %18 arttırdığı [13], armudun depolama süresini arttırdığı [14], şeker pancarında kalp çürümesinin azaldığı ve yumru ağırlığı verimini arttırdığı [15,16], tütün yaprağındaki nikotin içeriğini önemli şekilde arttığı [17], pamuk üretiminde verimi %11,68 arttığı [18], patlak mısır bitkisinde dane verimini arttığı [19], ayçiçeği üretiminde %10-%20 arasında değişen verim artışları görülmüştür [20]. Borun toprakta normal miktardan az olması, bitkilerin normal gelişimini etkilemekle onun verimini azaltmakla kalmayıp aynı zamanda, elde edilen ürünün kalitesini düşürür.…”
Section: Investigation Of the Utilization Of Borogypsum Industrial Waste For The Production Of Boron-containing Diammonium Phosphate 1girunclassified